A Review of the NANN Research Summit Experience: Continuing to Promote a Platform for Research and Clinical Inquiry. (February 2022) - Esser, Media S.; Shelley, Lauren; Moore, Tiffany A.
Abstract : Background: The NANN Research Summit has been providing a platform for neonatal scholarship and clinical inquiry for 15 years. As the discipline of nursing and nursing research continue to evolve, it is important to gain perspective on current trends and needs for areas of strength and growth. Purpose: To evaluate participant outcomes of the NANN Research Summit and determine opportunities for improvement. Methods: A 9-question survey was sent to 90 past participants for the Research Summit years 2015-2019. Results: Thirty-seven (41%) participants from 2015 to 2019 responded. Of those responding, 75% continued to pursue their presentation topic; 95% felt empowered to continue their research based on their Summit experience; 84% felt more comfortable presenting their research findings after attending; 84% felt confident in publishing research after attending the Summit, with 43% reporting publications. These accomplished results would not have been possible without Mead Johnson's support. In addition, 57% did not publish the work presented and 65% lacked continued mentorship. Implications for Practice: A redesigned Summit is presented to address the priorities for growth and alignment with continued emphasis on collegiality among neonatal nurse scholars. The redesigned Summit will promote continued clinical inquiry as a result of intentional focus on mentorship and development of scholarship. Implications for Research: The data collected from this initial survey will continue to serve as the basis for future data collection. Continued evaluation of strengths and areas for growth including the number of publications and mentorship experience can lead to expansion of research for the Summit facilitators and participants.